(3JWHjb GdTQjYI GdESdGejI aj eUQ (B: s (3OQGSI JWHjbjI Mhd GdfUhU GdOSJhQjI (B/ s - (3MGRe Ydj eGgQ s; (3CMeO ceGd CHh GdeLO (B: s; (3YHOGdYRjR QeVGf Sec (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2016)
(3jJdNU ehVhY gPg GdQSGdI aj Cfg HYO EbUGA GdTQjYI GdESdGejI Yf ecGfJgG GdMGceI ddYdGbGJ GdGLJeGYjI hGdSjGSjI hGdGbJUGOjI aj eUQ efP GdbQf GdJGSY YTQ(B: (3gjefJ GdOhdI GdMOjKI Ydi GdeLGdjf GdKbGaj hGdJTQjYj(B: (3hZjQgeG(B: (3hGcJaJ HJVejf HYV OSGJjQgG fUhUG ETcGdjI JJYdb HGdESdGe(B: (3eKd Cfg (B"(3Ojf GdOhdI(B": (3hCf (B"(3GdTQjYI GdESdGejI eUOQ QFjSj ddJTQjY(B." (3hbO GJSeJ gPg GdfUhU GdOSJhQjI HcKjQ ef GdZehV hGdYehe GdPj COi Edi EKGQI GdYOjO ef GdGdJHGSGJ hGdLOGdGJ Mhd eYGfjgG hBKGQgG(B: (3WQMJ eYXegG JMJ YfhGf (B"(3bVjI JWHjb GdTQjYI GdESdGejI(B": (3eeG GSJhLH GdHMK aj gPg GdfUhU ddfXQ aj eYGfjgG hOdGdGJgG(B: (3hGdSjGbGJ GdJGQjNjI hGdKbGajI hGdSjGSjI hGdGLJeGYjI GdJj hVYJ ajgG(B: (3hJbOje bQGAI fbOjI dLghO GdSdWGJ GdYGeI GdKdGK aj eUQ aj GdJYGed eYgG(B: (3aj eMGhdI ddhUhd Edi efgL hGVM aj age gPg GdfUhU HZjI GdESgGe aj JaYjdgG aj GdhGbY GdeYjT Ydi GdfMh GdPj jefY GdTbGb hGdJfGRY MhdgG hjecf dSjGOI GdTQjYI hGdbGfhf aj GdHdGO(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, (B2016. s
(3HHdjhLQGajG(B: (3UaMGJ (B-548: 578.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdTQjYI GdESdGejI aj eUQs; (3GdfUhU GdOSJhQjI s; (3eUOQjI GdTQjYI GdESdGejIs; (3GdSdWI GdJfajPjI s; (3OSJhQ (B1923s; (3OSJhQ (B1971s; (3GdTQjYI GdESdGejI aj eUQs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2016